Determination of heavy metals in herbal teas marketed in Istanbul - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2015)
Herbal teas are being used pretty much in Turkey. Besides having a lot of beneficial speciality, teas carry heavy metals in their structure and heavy metal pollution increase with environmental pollution. In this study; sage, rosemary, St. John'swort, linden, mint, thyme, chamomile, fennel, green tea, blueberries were used and lead and cadmium metals in this teas which were bought from herbalist, have been researched with Atomic Absorption Spectrophotometer. According to the results, cadmium and lead concentrations in all dried samples have been found in the limits of Turkish Food Codex.
Keywords: Herbal tea; heavy metal; atomic absorption; cadmium(II); lead(II)